Kinase PLK1 regulates the disassembly of the lateral elements and the assembly of the inner centromere during the diakinesis/metaphase I transition in male mouse meiosis - Gómez, Rocío; Viera, Alberto; Moreno-Mármol, Tania; Berenguer, Inés; Guajardo-Grence, Andrea; Tóth, Attila; Parra, María Teresa; Suja, José A. (Frontiers in Cell and Developmental Biology, 2023)
PLK1 is a serine/threonine kinase with crucial roles during mitosis. However, its involvement during mammalian male meiosis remains largely unexplored. By inhibiting the kinase activity of PLK1 using BI 2536 on organotypic cultures of seminiferous tubules, we found that the disassembly of SYCP3 and HORMAD1 from the lateral elements of the synaptonemal complex during diakinesis is impeded. We also found that the normal recruitment of SYCP3 and HORMAD1 to the inner centromere in prometaphase I spermatocytes did not occur. Additionally, we analyzed the participation of PLK1 in the assembly of the inner centromere by studying its implication in the Bub1-H2AT120ph-dependent recruitment of shugoshin SGO2, and the Haspin-H3T3ph-dependent recruitment of Aurora B/C and Borealin. Our results indicated that both pathways are regulated by PLK1. Altogether, our results demonstrate that PLK1 is a master regulator of the late prophase I/metaphase I transition in mouse spermatocytes.